Functional Efficiency and the Elements of the Political System: An Evaluation of Nigerian Political Structure and Restructuring Agenda - Okafor, Samuel O (Sociology Department Of Syiah Kuala University, 2021)
Nigerian political system much as other nations across the globe has been set up on a particular structure, which covertly dictates the rules for the manipulations of powers and the access to available resources. The understanding of this structure has enabled some groups (especially the political elites and ethnic cum religious majorities) to chart their way out of group related challenges while the ignorance of the structure has made other groups (the electorates and minority groups) in the same system vulnerable to the inordinate ambitions of other groups. Hierarchies of governments in Nigeria such as federal, state and local governments reflect in their nature, opportunities and vulnerabilities for different categories of people of which if properly understood and utilised, will be more service oriented than theoretical assumption. This paper examines the ideal political structures of Nigerian political system, considering the roles of the elements in these structures, their pragmatic implications to the hope of the masses in Nigeria and the harmony of the Nigerian political system. This was carried out with the aid of structural functionalism and game theoretical models. Standing on the angle of utilitarian values of structures, the paper recommends the populists' approach to the Nigerian political structure by the common citizens for the reconciliation of the challenges of multi-ethnic cum religious interests and the crises of the political elites in Nigerian political system